PATTERNS OF FARMING FINANCING AMONG CORN FARMERS IN BUN BUN ALAS VILLAGE - Sihotang, Mutiah Khaira; Alfarisi, Salman (Proceeding International Seminar of Islamic Studies, 2024)
The agricultural sector in Indonesia is the leading sector in the nation's economic growth, including creating jobs and reducing poverty. Based on data from the Central Statistics Agency (BPS), the role of the agricultural sector as a provider of employment opportunities has not yet been replaced. Corn farmers are one source of income for the people of Kutacane, Southeast Aceh Regency. However, there are still people who are unable to cultivate the land they own due to limited capital. This is because this location is not accessible to Islamic financial institutions. However, farmers have their own financing patterns to meet the capital needed. The research aims to determine the analysis of corn farming financing patterns in Kutacane using qualitative research methods. There are two sources of data, namely primary data and secondary data. Primary data was collected from all respondents through interviews using a list of prepared questions and also observations. Meanwhile, secondary data was obtained from libraries, literature and related agencies. Based on the results of research conducted, financing patterns for corn farmers in Kutacaen include independent financing, private financing, land processing financing and government financing.